Differences in multielement concentrations in rice (Oryza sativa L.) between longevity and non-longevity areas in China and their relations with lifespan indicators. (December 2022) - Xia, Meng-Chan; Du, Yajun; Zhang, Shixi; Feng, Jiaxin; Luo, Kunli
Graphical abstract: Highlights: We found differences in multielement concentrations in rice among SLs, SNLs and NNLs. Rice from SLs was characterized by high concentrations of K, Mg, P, Mn and Ni. Rice intake provided greater proportions of the dietary mineral requirements in SLs. K concentration in rice was significantly positively correlated with lifespan indicators. Abstract: Geographical distribution pattern of centenarians in China runs counter to the global trend, and centenarians are mainly distributed in low-latitude South China but rarely in high-latitude North China. To investigate the effect of the elemental content of rice on the differences between the longevity areas and the non-longevity areas in China, the multielement concentrations in 84 rice samples collected from 28 counties/cities were measured, of which 37 belonged to the longevity areas in South China (SLs), 36 belonged to non-longevity areas in South China (SNLs), and 11 belonged to non-longevity areas in North China (NNLs). The concentrations of 29 different elements (Ca, K, Mg, Na, P, S, Se, As, Ba, Cr, Cu, Fe, Mn, Mo, Ni, Sr, Ti, Zn Cd, Co, Li, Pb, Tl, Cs, Ga, In, Rb, U and Bi) in rice samples were determined by ICP-OES, ICP-MS and HG-AFS. Notably, the concentrations of macroelements in SLs rice samples (3682.92 mg/kg) were significantly higher than those of SNLs (3046.62 mg/kg) and NNLs (2590.38 mg/kg) ( p  < 0.05). The concentrations of essential microelements in rice samples of SLs (38.87 mg/kg) and NNLs (41.79 mg/kg) were not significantly different, but both significantly higher than those of SNLs (31.91 mg/kg) ( p  < 0.05). Significant differences were also found in the concentrations of K, Mg, Na, P, S, Cu, Mn, Mo, Ni, Pb, Tl, In and Cs in rice among SLs, SNLs and NNLs ( p  < 0.05). The rice samples of SLs had the characteristic of higher concentrations of K, Mg, P, Mn and Ni. Thus, rice intake in SLs provided greater proportions of the dietary mineral requirements than those in SNLs and NNLs. Besides, the concentrations of K, Mg, P, Ni and Ti in rice, especially K, were demonstrated to be significantly positively correlated with lifespan indicators ( p < 0.05 ), while the concentrations of Ga, Cd, In and U in rice were negatively correlated with lifespan indicators. Our findings are expected to provide a basis for reasonable dietary mineral element intakes and promote understanding of the relationships between natural environment and regional longevity in China.